An object-oriented approach to the rapid prototyping of courseware : Instructional design considerations and method. - Seong , Chong Toh (1995)

(untitled)
The object-oriented programming paradigm (OOP) has revolutionized the software development process. This paper discusses the instl1lctional design considerations in the development of a shell using the OOP paradigm to enable courseware authors to create courseware rapidly through rapid prototyping.